DEVELOPMENT STRATEGY OF NATURAL TOURISM IN PANCAR MOUNTAIN NATURAL PARK - Arde Lindung Pambudi; Arief Daryanto; Sri Hartoyo (Jurnal Manajemen dan Wirausaha, 2014)
The purposes of this study are to identify the internal and external factors and to determine the best strategy for developing natural tourism in Pancar Mountain Natural Park. This study employs a descriptive method through surveys using a purposive sampling method. The analysis tools used are IFE and EFE, IE Matrix, SWOT Matrix and QSPM. Recommended strategies are: 1) product development strategy, 2) market penetration, 3) optimizing the cooperation of stakeholders, 4) defining the area and boundary of Pancar Mountain Natural Park, 5) increasing citizen participation and 6) increasing the role of associations.